Historical Changes of Values on Diligence and Indolence - Мионг, Сун Ок, Ок,; Чaн, Бенг Сун Сун; Aльджaновa, Н. (Journal of Oriental Studies, 2017)
In this era the person who is considered idle is condemned. However, seeing laziness is not always negative throughout the human history. The dichotomy of values between idleness and diligence has been strengthened historically and culturally along with the impact of industry revolution, protestant spirit, and capitalism. Actually, the logic of power accompanied by cultural repression is concealed behind the value judgment of diligence and laziness.